The Evolution and Evaluation of Massive Open Online Courses MOOCs in Motion - Waks, Leonard J. (The Cultural and Social Foundations of Education, 2016)
This book offers a re-assessment of the educational and occupational value of MOOCs based on developments since 2013. When MOOCs appeared amidst great fanfare in 2012, leaders proclaimed an educational "revolution." By 2013, however, dramatic failures, negative research findings, and sharp critiques ended the MOOC hype. This book examines both MOOCs and prior distance learning innovations, and offers a broad overview of their educational, economic and social effects. Chapters explore ties between MOOCs and emerging pedagogical models as well as exponentially rising tuition rates, student debt, and chronic underemployment of university graduates worldwide. It offers readers a comprehensive, up-to-the-moment guide to the MOOC phenomenon. Leonard J. Waks is Professor Emeritus of Educational Leadership at Temple University, USA.